(untitled) (Fiep Bulletin - online, 2013)
The research checked the perception that coaches of individual and team sports have regarding characteristics of creative athletes. The instrument used: a questionnaire with 35 statements representing behaviors and creative production. Subjects: 66 coaches of 12 sport events. Sensitivity to problems was the most mentioned characteristic in team events and originality in individual events. Negative aspects of behavior (level of demand and negative leadership) are mentioned more in team events, as well as the difficulty of fulfilling commitments and challenging others. Positive personal aspects, such as courage, determination and discipline are also perceived by coaches of team events.